Epidemiological Profile of Acute Myocardial Infarction Mortality from 2013 to 2023 in Brazil - Santos, Pedro Henrique Amorim Moura dos; de Sousa Neto, Mário Leite; Matias, Luiz Amadeu de Sousa Nogueira; Alencar, Carlos Eduardo; Silva, Kahuã Andrade; Nascimento, Roberto César de Arêa Leão; Rios, Nelson Agapito Brandão (Archives of Community Medicine and Public Health, 2024)
Introduction: Cardiovascular diseases are the leading cause of death worldwide, accounting for more than 30% of deaths in Brazil, especially due to Acute Myocardial Infarction (AMI). This study aims to outline the epidemiological profile of AMI deaths in Brazil between 2013 and 2023, analyzing the main variables. Methodology: This is an ecological study on AMI mortality in Brazil from 2013 to 2023, focusing on identifying epidemiological and regional patterns. The research covered the entire national territory, divided into five regions (North, Northeast, Central-West, Southeast, and South), considering distinct sociodemographic characteristics. Data on AMI deaths were collected from the Mortality Information System (SIM) of DATASUS, classified according to ICD-10. The variables analyzed included sex, geographic region, age group, education level, and race/color. Results: Between 2013 and 2023, Brazil recorded 1,017,263 deaths from AMI, with a predominance of male deaths (59.1%). The year 2022 had the highest number of deaths (98,019), while 2013 had the lowest (85,939). Statistical analysis indicated an increasing trend in deaths over the decade. Regarding race/color, the white population was the most affected, accounting for 52.06% of deaths, followed by the brown population (36.70%) and the black population (7.91%). Discussion: The highest mortality rates occurred in the Southeast and South regions, reflecting population density and aging. The white population accounted for 52.1% of deaths, while individuals with lower education levels showed higher mortality. Although some studies indicate a reduction in cardiac mortality rates, the data from this study suggest an increase.